2022
DOI: 10.1186/s13102-022-00569-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between high physical activity and premenstrual syndrome in Japanese female college students

Abstract: Background In recent years, moderate physical activity has attracted the attention of experts and women as a way to cope with premenstrual syndrome (PMS). Studies investigated the effects of exercise on PMS, but only a few reports focused on the relationship between physical activity, which included not only exercise but also routine bodily movements, and PMS. Therefore, the present study investigated the relationship between the amount of physical activity and PMS symptoms among sexually matur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…This finding may suggest that individuals with more severe PMS symptoms may exercise less due to the impact of the symptoms on their physical activity. Alternatively, this finding may be consistent with the existing literature, where increased physical activity has been found to reduce PMS symptoms [ 57 - 62 ]. In attempting to fill the research gap regarding sleep patterns across the menstrual cycle, we did not make any notable discoveries when comparing sleep duration between different phases of the menstrual cycle, across PMS severity, or when comparing individuals using hormonal contraception with those who did not.…”
Section: Discussionsupporting
confidence: 91%
“…This finding may suggest that individuals with more severe PMS symptoms may exercise less due to the impact of the symptoms on their physical activity. Alternatively, this finding may be consistent with the existing literature, where increased physical activity has been found to reduce PMS symptoms [ 57 - 62 ]. In attempting to fill the research gap regarding sleep patterns across the menstrual cycle, we did not make any notable discoveries when comparing sleep duration between different phases of the menstrual cycle, across PMS severity, or when comparing individuals using hormonal contraception with those who did not.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the intensity of PA, we also examined participant energy consumption and found that Kcals were linked with PMS. Kawabe et al suggested that a total PA of ≥ 3000 metabolic equivalent minutes/week was associated with milder PMS symptoms irrespective of PA intensity [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…PMS can lead to significant distress and a decline in functional capacity. [1][2][3][4][5] Previous studies have indicated a relatively high frequency of PMS. Worldwide, it has been reported that approximately 47.8% of reproductive-age women are affected by PMS, with 5%-8% experiencing moderate to severe symptoms that are related to functional impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Common manifestations of PMS include alterations in appetite, irritability, depression, anxiety, difficulty concentrating, headaches, weight gain, constipation, fatigue, abdominal and lower back pain, breast swelling and tenderness, as well as mood swings. PMS can lead to significant distress and a decline in functional capacity 1–5 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation